205k views
3 votes
Simplify. 5 - [ - ( - 2)]

2 Answers

3 votes

Answer:

3

Explanation:

1. A - times a - equals a +, which means [-(-2)] equals (2)

2. 5- (2) equals 5 - 2

3. 5-2= 3

User Ali Tor
by
5.5k points
4 votes

Answer:

3

Explanation:

As you see in the equation, there is a simple rule to apply in any equation make you confuse with - or + symbol. When 2 minus symbol ( - ) stand together, it would become positive or plus symbol (+), so in this situation:

5 - [ - ( - 2)]

= 5 - (+ 2)

= 5 - 2

= 3

Hope this help you :3

User Tovah
by
6.6k points